MODERN PARADIGM OF THE ECONOMIC THEORY - Koryun K. Antonyan (Статистика и экономика, 2016)
The article considers the question whether the economic theory copes with its role of methodological and theoretical spotlight, backlighting the way of development. The article discusses also processes in the political economy, its fate in the current situation.